Nonlinear the first kind Fredholm integro-differential first-order equation with degenerate kernel and nonlinear maxima - Yuldashev, T. K.; Eshkuvatov, Z. K.; Nik Long, N. M. A. (Lviv Polytechnic National University, 2022)
In this note, the problems of solvability and construction of solutions for a nonlinear Fredholm one-order integro-differential equation with degenerate kernel and nonlinear maxima are considered. Using the method of degenerate kernel combined with the method of regularization, we obtain an implicit the first-order functional-differential equation with the nonlinear maxima. Initial boundary conditions are used to ensure the solution uniqueness. In order to use the method of a successive approximations and prove the one value solvability, the obtained implicit functional-differential equation is transformed to the nonlinear Volterra type integro-differential equation with the nonlinear maxima.